ON THE SYNTHESIS OF NUCLEIC ACIDS AND THEIR ROLE IN THE PRESERVATION AND TRANSMISSION OF INHERITED TRAITS OF THE ORGANISM (Eureka Journal of Health Sciences & Medical Innovation, 2025)
This article discusses the synthesis of nucleic acids, their storage and transmission of hereditary traits in the body, as well as the mechanisms that preserve DNA within cells (DNA repair, replication, and chromosome organization with histones). You will learn how these processes protect against mutations and maintain the integrity of the genetic code.
Keywords: Nucleoside 5-triphosphates, nitrogenous base, pentose, phosphoric acid, heterocyclic rings, carbamyl phosphate, guanylic acid.